All-solid-state lithium ion battery and application thereof

By depositing an ion conductor layer composed of ether polymer, lithium salt and metal fluoride on the surface of the lithium metal negative electrode, a stable negative electrode-solid electrolyte interface layer is formed, and the air stability and interface impedance problems of sulfide all-solid lithium-ion batteries are solved, and the cycling performance and electrochemical performance of the battery are significantly improved.

CN119695247AActive Publication Date: 2025-03-25ENVISION DYNAMICS TECH (JIANGSU) CO LTD +1
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411926254.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-25
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The air stability of sulfide all-solid lithium-ion batteries is poor, easily reacting with water to release highly toxic gases, and the sulfide solid electrolyte is easily chemically reduced by nucleophilic lithium metal, resulting in an increase in interface impedance and poor circulation performance.

Method used

By depositing a layer of ion conductor layer composed of ether polymer, lithium salt and metal fluoride on the surface of the lithium metal negative electrode, a stable negative electrode-solid electrolyte interface layer is formed to prevent the reduction and decomposition of the sulfide solid electrolyte and improve the conductivity of the interface to lithium ions.

Benefits of technology

Effectively reduce the interface impedance, enhance the cycling and electrochemical properties of the battery, improve the conductivity stability and air stability of sulfide solid electrolytes, and reduce the risk of lithium dendrites.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210278890000191
    Figure BDA0005210278890000191
Patent Text Reader

Abstract

The invention provides an all-solid-state lithium ion battery and application thereof. The all-solid-state lithium ion battery comprises a positive pole piece and a negative pole piece, the lithium metal negative electrode comprises a lithium matrix and an ion conductor layer arranged on one side of the lithium matrix, and the ion conductor layer comprises an ether polymer, a lithium salt and a metal fluoride; a solid electrolyte membrane is arranged between the positive pole piece and the lithium metal negative pole, an ion conductor layer is arranged close to the solid electrolyte membrane, the solid electrolyte membrane comprises a sulfide solid electrolyte, and the chemical formula of the sulfide solid electrolyte is LiaP1-bMbScOdXe, a < lt >; 6, 0lt; blt; 1, 1.5 1t; clt; ct; 5, 0lt; dlt; 2.5, 4lt; c + dlt; 5, 1lt; lt, lt; 2; m is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V or Nb, and X is selected from one or more of Cl, Br or I. According to the all-solid-state lithium ion battery and the application thereof provided by the invention, the air stability of the sulfide solid electrolyte can be improved, and the electrochemical performance of the sulfide all-solid-state lithium ion battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to an all-solid-state lithium ion battery and applications thereof. Background Art

[0002] Sulfide all-solid-state lithium-ion batteries use high-ionic conductivity sulfide solid electrolytes to replace traditional organic liquid electrolytes and separators, which can simplify battery design and greatly improve battery safety. They also have the advantages of high safety performance, high energy density, and a wide operating temperature range. However, the mass production of sulfide all-solid-state lithium-ion batteries still faces many challenges, such as the poor air stability of sulfide solid electrolytes, which react with water to cause a sharp deterioration in performance and release of highly toxic hydrogen sulfide gas. In addition, sulfide solid electrolytes are easily chemically reduced by nucleophilic lithium metals, and the resulting side reactions will greatly increase the interfacial impedance, resulting in poor cycle performance of all-solid-state lithium-ion batteries.

[0003] Surface coating or doping of sulfide solid electrolytes can effectively improve the stability and safety of sulfide solid electrolytes in the air, and can also alleviate the side reactions at the interface to a certain extent. However, long-term cycle results show that only modification of sulfide solid electrolytes can still lead to severe degradation of interface impedance or battery short circuit. Summary of the invention

[0004] The present invention proposes an all-solid-state lithium ion battery and applications thereof. Through the all-solid-state lithium ion battery and applications thereof provided by the present invention, the stability of the electrical conductivity of the sulfide solid electrolyte can be improved, the air stability can be enhanced, the sulfide solid electrolyte reacts with the ion conductor layer to jointly form a stable negative electrode-solid electrolyte interface layer, which can effectively reduce the interface impedance, block the reduction decomposition of the sulfide solid electrolyte, and improve the electrochemical performance of the sulfide all-solid-state lithium ion battery.

[0005] To solve the above technical problems, the present invention is implemented through the following technical solutions.

[0006] The present invention provides an all-solid-state lithium-ion battery, comprising at least:

[0007] Positive electrode;

[0008] A lithium metal negative electrode, the lithium metal negative electrode comprising a lithium matrix and an ion conductor layer disposed on one side of the lithium matrix, the ion conductor layer comprising an ether polymer, a lithium salt and a metal fluoride; and

[0009] A solid electrolyte membrane is arranged between the positive electrode and the lithium metal negative electrode, the ion conductor layer is arranged close to the solid electrolyte membrane, and the solid electrolyte membrane includes a sulfide solid electrolyte, and the chemical formula of the sulfide solid electrolyte is Li a P1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, and X is selected from one or more of Cl, Br, or I.

[0010] In one embodiment of the present invention, M is selected from at least one of Sb, In, or Bi, and X is selected from Cl.

[0011] In one embodiment of the present invention, the ether polymer is formed by ring-opening polymerization of ether monomers, and the ether monomers include one or more combinations of 1,3-dioxolane, tetrahydrofuran, propylene oxide, chloromethyl ethylene oxide, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether, or pentaerythritol glycidyl ether.

[0012] In one embodiment of the present invention, the lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluoro(oxalato)borate, lithium difluoro(oxalato)phosphate, lithium bis(oxalato)borate, or lithium difluorophosphate.

[0013] In one embodiment of the present invention, the cation in the metal fluoride includes Ag + , Al 3+ , Zn 2+ , Mg 2+ or Sn 2+ or one or more of them, and the anion in the metal fluoride includes F - , PF6 - , FSI - , TFSI - , BF4 - , PF2O2 - , ODFB - or ODFP - or one or more of them.

[0014] In one embodiment of the present invention, the ion conductor layer is deposited on the surface of the lithium matrix by spraying or doctor blading, and the thickness of the ion conductor layer is 0.2 μm to 10 μm.

[0015] In one embodiment of the present invention, in the ion conductor layer, the mass ratio of the ether polymer, the lithium salt, and the metal fluoride is 60 to 89.5:10 to 30:0.5 to 10.

[0016] In one embodiment of the present invention, the thickness of the solid electrolyte membrane is 30 μm to 100 μm.

[0017] In one embodiment of the present invention, the solid electrolyte membrane includes a sulfide solid electrolyte and a binder, and the content of the sulfide solid electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

[0018] The present invention also provides an electronic device, comprising the all-solid-state lithium-ion battery described above.

[0019] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide solid electrolyte, enhance the air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. The ion conductor layer has good compatibility with the lithium matrix, can effectively block the direct contact between the sulfide solid electrolyte and the lithium matrix, and inhibit the continuous reaction of the sulfide solid electrolyte. The ion conductor layer has better flexibility, can better accommodate the volume change during lithium deposition / stripping, and can alleviate the volume expansion of the lithium metal negative electrode. By forming a layer of organic-inorganic composite ion conductor layer, the interface impedance can be effectively reduced, the reduction and decomposition of the sulfide solid electrolyte can be blocked, and the electrochemical performance of the sulfide all-solid-state lithium-ion battery can be improved. The sulfide solid electrolyte reacts with the ion conductor layer to form a stable negative electrode-solid electrolyte interface layer. The interface layer has good ionic conductivity and electronic insulation. This stable interface layer can block the direct contact between the sulfide solid electrolyte and the lithium metal negative electrode, and can also make the current and Li on the interface + The flux is homogenized to reduce the risk of lithium dendrite formation. DETAILED DESCRIPTION

[0020] The following describes the embodiments of the present invention through specific examples, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific embodiments, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0021] It should be understood that the present invention can be implemented in different forms and should not be interpreted as limited to the embodiments set forth herein. On the contrary, these embodiments are provided to make the disclosure thorough and complete and to fully convey the scope of the present invention to those skilled in the art.

[0022] The technical solution of the present invention is further described in detail below in conjunction with several embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The present invention provides an all-solid-state lithium-ion battery, which includes a positive electrode sheet, a lithium metal negative electrode, and a solid electrolyte membrane. In the present invention, the all-solid-state lithium-ion battery is, for example, a primary battery or a secondary battery, and the secondary battery is, for example, a soft-pack battery, a hard-shell battery, or a cylindrical battery. The present invention does not specifically limit the type and type of the all-solid-state lithium-ion battery.

[0024] In one embodiment of the present invention, the lithium metal negative electrode includes a lithium matrix and an ion conductor layer disposed on one side of the lithium matrix, and the ion conductor layer includes an ether polymer, a lithium salt and a metal fluoride. Among them, the lithium matrix is, for example, a lithium electrode plate. The ether polymer is formed by ring-opening polymerization of ether monomers, and the ether monomers include, for example, 1,3-dioxolane, tetrahydrofuran, propylene oxide, chloromethyl ethylene oxide, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether or pentaerythritol diglycidyl ether. These ether monomers are selected from cyclic ethers, and the cyclic ethers can undergo ring-opening polymerization under the action of lithium salts to form ether polymers with different polymerization degrees. These ether polymers have good compatibility with the lithium matrix, adhere to the surface of the lithium matrix, and can effectively block the direct contact between the sulfide solid electrolyte and the lithium matrix, and inhibit the continuous reaction of the sulfide solid electrolyte. When the ether monomer is a monocyclic ether, ring-opening polymerization forms a linear ether polymer, and when the ether monomer is a polycyclic ether, ring-opening polymerization forms a cross-linked ether polymer. When monocyclic ether and polycyclic ether exist at the same time, the generated cross-linked ether polymer has better flexibility and can better accommodate the volume change during lithium deposition / stripping.

[0025] In one embodiment of the present invention, the lithium salt includes, for example, lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium dioxalate borate or lithium difluorophosphate. As a carrier of ion conduction, the lithium salt cation has a strong intermolecular force with the ether oxygen bond of the ether polymer. The lithium ion (Li + ) As the ether oxygen bond vibrates, it quickly migrates between molecular chains to conduct ions. The anions of lithium salts can decompose to form Lewis acidic groups, which can act as initiators to initiate the ring-opening polymerization of cyclic ethers to form chain ether polymers. The formed ether polymers can alleviate the volume expansion of lithium metal negative electrodes. Furthermore, the anions are reduced and decomposed on the surface of the lithium matrix to form inorganic layers rich in Li3B, Li3P and Li3N, which can regulate the interface Li+ Conductivity and deposition behavior, inhibiting the formation of lithium dendrites. By forming a layer of organic-inorganic composite ion conductor layer, it can effectively reduce the interface impedance and block the reduction and decomposition of sulfide solid electrolytes, thereby improving the electrochemical performance of sulfide all-solid-state lithium-ion batteries.

[0026] In one embodiment of the present invention, the cations in the metal fluoride include Ag + 、Al 3+ 、Zn 2+ Mg 2+ or Sn 2+ One or more of the above, wherein the anions in the metal fluoride include F - PF6 - 、FSI - TFSI - 、BF4 - PF2O2 - 、ODFB - or ODFP - One or more of the above. The cations of metal fluoride can form a lithium alloy phase on the surface of lithium metal, which can quickly convert Li + The lithium fluoride anions are transported from the lithium metal surface to the solid electrolyte membrane interface to compensate for the loss of lithium, and the metal fluoride anions generate LiF with low electronic conductivity at the two-phase interface (i.e., the surface of the ion conductor layer).

[0027] In one embodiment of the present invention, the ion conductor layer is deposited on the surface of the lithium metal negative electrode by spraying or scraping, for example, and the specific steps include:

[0028] Weighing an ether monomer, a lithium salt and a metal fluoride according to a mass ratio, adding them into a solvent, and mixing to obtain a uniform mixture;

[0029] depositing the mixture on a surface of a lithium substrate;

[0030] The in-situ ring-opening polymerization reaction is carried out at a preset temperature and for a preset time to obtain a lithium metal negative electrode with an ion conductor layer on the surface.

[0031] In one embodiment of the present invention, the mass ratio of the ether monomer, the lithium salt and the metal fluoride is, for example, 60-89.5:10-30:0.5-10. Specifically, the total weight of the ether monomer, the lithium salt and the metal fluoride is 100%, the proportion of the ether monomer is, for example, 60%, 70%, 80% or 85%, the proportion of the lithium salt is, for example, 10%, 15%, 20% or 30%, and the proportion of the metal fluoride is, for example, 1%, 5%, 10%. The solvent is, for example, selected from at least one of ethylene glycol dimethyl ether (1,2-dimethoxyethane, DME), dimethyl carbonate (Dimethyl Carbonate, DMC), ethyl methyl carbonate (Ethyl Methyl Carbonate, EMC) or acetonitrile (Acetonitrile, AN), and in the mixture, the content of the solvent is, for example, 10wt% to 40wt%. The ion conductor layer is deposited on the surface of the lithium substrate by spraying or scraping.

[0032] In one embodiment of the present invention, the preset temperature is, for example, 30°C to 50°C, and the preset time is, for example, 2h to 10h. During the standing process, the ether monomers undergo ring-opening polymerization under the action of lithium salts to form ether polymers that adhere to the surface of the lithium matrix, the metal fluoride cations form lithium alloy phases on the surface of the lithium matrix, and the metal fluoride anions generate LiF with low electronic conductivity on the surface of the ion conductor layer. During the standing process, the solvent evaporates, and at the same time, part of the ether monomer evaporates along with the solvent, and the thickness of the formed ion conductor layer is, for example, 0.2μm to 10μm, and for example, 0.2μm, 2μm, 5μm or 10μm. When the thickness of the ion conductor layer is thin, the inorganic layer formed at the interface is thin, and long-term lithium deposition / stripping results in huge volume changes, resulting in the rupture of the inorganic layer and the formation of lithium dendrites. When the ion conductor layer is thicker, since the ionic conductivity of the ion conductor layer is lower than that of the sulfide solid electrolyte, Li + It takes more time to pass through this membrane, which will deteriorate the rate performance and energy density of all-solid-state lithium-ion batteries.

[0033] In one embodiment of the present invention, in the ion conductor layer, the mass ratio of the ether polymer, the lithium salt and the metal fluoride is 60-89.5:10-30:0.5-10. Among them, when the content of the lithium salt and the metal fluoride is low, the carrier concentration of the ion conductor layer is low, the ion conduction is hindered, and the lithium alloy and LiF generated on the surface of the lithium matrix are thin, and lithium dendrites still appear during long-term circulation. When the content of the lithium salt and the metal fluoride is high, the relative content of the ether monomer is low, the strength of the ether polymer formed after the ring-opening polymerization decreases, and a large amount of lithium salt and metal fluoride are deposited on the surface of the lithium matrix, which is not conducive to ion transmission, thereby affecting the performance of the battery. By controlling the thickness of the ion conductor layer and the mass ratio of the ether polymer, the lithium salt and the metal fluoride, the performance of the battery can be improved.

[0034] In one embodiment of the present invention, a solid electrolyte membrane is disposed between the positive electrode sheet and the lithium metal negative electrode, and an ion conductor layer is disposed close to the solid electrolyte membrane. The solid electrolyte membrane includes a sulfide solid electrolyte, and the chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, etc., and X is selected from one or more of Cl, Br, or I, etc. Introducing M element and O element into the sulfide solid electrolyte rich in halogen elements will form P-O and M-S bonds in the crystal structure, thereby improving the inherent resistance to atmospheric degradation and effectively reducing the generation of H2S, enhancing the air stability and chemical stability of the sulfide solid electrolyte. In addition, when using this sulfide solid electrolyte to assemble an all-solid-state lithium-ion battery, the doped and modified sulfide solid electrolyte forms LiCl with a higher interfacial energy and Li2O with a higher ionic conductivity at the interface with the negative electrode. At the same time, the sulfide solid electrolyte reacts with the ion conductor layer to form LiF and Li3N, etc. LiF, Li2O, Li3N, LiCl, and the ether polymer formed by ring-opening polymerization together constitute a stable negative electrode-solid electrolyte interface layer. This interface layer has good ionic conductivity and is electronically insulating. This stable interface layer can block the direct contact between the sulfide solid electrolyte and the lithium metal negative electrode, and at the same time, it can also equalize the current and Li + flux on the interface, reducing the risk of lithium dendrite formation.

[0035] In one embodiment of the present invention, M is, for example, selected from at least one of Sb, In, or Bi. Since the ionic radii of Sb, In, or Bi are moderate, the ionic radii of these elements are close to those of the main elements in the sulfide solid electrolyte, such as sulfur and phosphorus, etc. Therefore, during doping, they can more easily replace the positions of the main elements without causing excessive lattice distortion. And the electronegativity of Sb, In, or Bi is moderate, and they can form stable chemical bonds with the sulfur element in the sulfide, and are difficult to be damaged by external influences. Thus, the sulfide solid electrolyte has high stability and specific reactivity, can improve the stability of the ionic conductivity of the sulfide solid electrolyte, enhance the air stability, and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material.

[0036] In one embodiment of the present invention, X is selected from halogen elements, and depending on the halogen, the degree of anion disorder between the 4a and 4c sites in the crystal structure of the sulfide solid electrolyte is different, ranging from a small amount of anti-site defects when X is I to 60% site disorder when X is Cl, and the lithium conductivity of these compounds mainly depends on the degree of disorder occupied by anion and cation sites. Therefore, X is selected from Cl, for example, to improve the ionic conductivity and electrochemical stability of the sulfide solid electrolyte and improve voltage stability. The value range of b is 0<b≤0.1. In a specific embodiment of the present invention, when M is +5 valence, b is optimally 0.04, and when M is +3 valence, b is optimally 0.02, so as to improve the cycle performance of the lithium ion battery.

[0037] In one embodiment of the present invention, the sulfide solid electrolyte is obtained by the following preparation method: according to the chemical formula of the sulfide solid electrolyte, the Li source, the P source, the M source, the S source and the X source are mixed according to the stoichiometric ratio, and the mixture is placed in a ball mill for ball milling to obtain a sulfide solid electrolyte precursor powder; the sulfide solid electrolyte precursor powder is calcined at a preset temperature to obtain a sulfide solid electrolyte.

[0038] In one embodiment of the present invention, according to the chemical formula of the sulfide solid electrolyte Li a P 1-b M b S c O d X e , the Li source, P source, M source, S source and X source are uniformly mixed according to stoichiometric ratio, wherein the Li source is selected from one or more of LiCl, LiBr, LiI or Li2S, the P source is selected from one or more of elemental P, P2S5, P4S6, PCl5 or PBr5, the M source is selected from one or more of oxides of M or sulfides of M, the S source is selected from one or more of elemental S, Li2S, P2S5, P4S6, As2S5, As2S3, Sb2S5, Sb2S3, Bi2S5, Bi2S3, Al2S3, Ga2S3, In2S3 or Sc2S3, the X source is selected from one or more of LiCl, PCl5, LiBr, PBr5, LiI or I2, and the O element in the chemical formula comes from the oxide of M. After the raw materials are evenly mixed, they are placed in a ball mill and ball milled in an inert gas atmosphere, wherein the ball-to-material ratio is, for example, 1:1 to 100:1, the ball milling speed is, for example, 50 rpm to 1500 rpm, and the ball milling time is, for example, 1 h to 48 h, to obtain a sulfide solid electrolyte precursor powder.

[0039] In one embodiment of the present invention, the sulfide solid electrolyte precursor powder is calcined at a preset temperature, wherein the preset temperature is 400°C to 600°C, and the calcination time is 1h to 18h, to obtain a sulfide solid electrolyte. In one embodiment of the present invention, the particle size of the sulfide solid electrolyte is, for example, 1μm to 10μm, and the ionic conductivity is greater than 3mS / cm.

[0040] In one embodiment of the present invention, after obtaining the sulfide solid electrolyte, a solid electrolyte membrane is obtained, for example, by dry preparation or wet preparation. In this embodiment, for example, the solid electrolyte membrane is obtained by dry preparation, specifically, the sulfide solid electrolyte and the binder are blended according to the mass ratio to obtain a mixed powder; the mixed powder is repeatedly rolled at a preset temperature for a preset time to obtain a solid electrolyte membrane. Among them, the content of the sulfide solid electrolyte in the solid electrolyte membrane is, for example, 80wt% to 99wt%, and the binder is, for example, selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binders, silicone rubber, styrene butadiene rubber, nitrile rubber or hydrogenated nitrile rubber. The preset temperature is 60℃ to 100℃, the preset rolling time is 30min to 120min, and the thickness of the obtained solid electrolyte membrane is, for example, 30μm to 100μm.

[0041] In one embodiment of the present invention, the positive electrode sheet includes, for example, a positive electrode current collector and a positive electrode active layer disposed on at least one side of the positive electrode current collector. The positive electrode current collector is, for example, a foil formed by surface treatment of nickel, titanium, aluminum, silver, stainless steel or carbon. In addition to the foil, the positive electrode current collector can also be used in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric, and the thickness of the positive electrode current collector is, for example, 8 μm to 15 μm.

[0042] In one embodiment of the present invention, the positive electrode active layer includes, for example, a positive electrode active material, a positive electrode electrolyte, a conductive agent, and a binder, wherein the positive electrode active material is selected from, for example, a positive electrode active material with a layered structure, such as one or more combinations of lithium cobalt oxide (LCO), nickel cobalt manganese lithium oxide (NCM), or nickel cobalt aluminum lithium oxide (NCA). The positive electrode active material is selected from, for example, an olivine structured positive electrode active material, such as one or more combinations of lithium iron phosphate (LFP) or lithium iron manganese phosphate (LFMP). The positive electrode active material is selected from, for example, a spinel structured positive electrode active material, such as one or more combinations of lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), or lithium-rich manganese-based (LMR).

[0043] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05O2, wherein the coating layer has a thickness of, for example, 5 nm to 15 nm. In this embodiment, the positive electrode active material is obtained, for example, by a wet coating method. By coating with LiNbO3, the discharge capacity and cycle stability of the all-solid-state lithium-ion battery can be improved, the mechanical properties of the material can be enhanced, and the service life of the battery can be extended.

[0044] In one embodiment of the present invention, the positive electrode electrolyte is, for example, the above-mentioned sulfide solid electrolyte. The conductive agent is, for example, selected from one or more combinations of conductive carbon black (Super P), nanocarbon fiber (Vapor-grown Carbon Fiber, VGCF), Ketjen black, acetylene black, graphene, carbon nanotubes, porous carbon, etc., and the binder is, for example, selected from one or more combinations of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polytetrafluoroethylene (PTFE), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR), etc.

[0045] In one embodiment of the present invention, the positive electrode active material is, for example, LiNbO3 coated LiNi 0.9 Co 0.05 Mn 0.05 O2, the positive electrode electrolyte is, for example, the above-mentioned sulfide solid electrolyte, the conductive agent includes, for example, Super P and VGCF, and the mass ratio of Super P and VGCF is, for example, 1:1, and the binder is, for example, HNBR. The positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in a low-polarity solvent such as xylene according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to be, for example, about 55%. The slurry is coated on the aluminum foil by a doctor blade method, and the coated aluminum foil is air-dried at 90°C to 110°C for 2h to 3h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, and the thickness of the positive active layer is, for example, 80μm to 120μm. The present invention does not limit the mass ratio of the positive electrode active material, the positive electrode electrolyte, the positive electrode conductive agent and the positive electrode binder, and can be selected according to actual needs.

[0046] In one embodiment of the present invention, the above-mentioned positive electrode sheet, solid electrolyte membrane and lithium metal negative electrode are placed in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the lithium metal negative electrode to play an isolating role, and the sheets are stacked to form a bare cell. The bare cell is placed in a shell and sealed, and the shell is, for example, an aluminum-plastic bag, etc., and then the process of standing, forming and dividing the capacity is carried out to obtain a finished soft-pack solid-state lithium-ion battery. Among them, the assembly process of the all-solid-state lithium-ion battery is completed in a glove box with an inert atmosphere.

[0047] Hereinafter, the present invention will be explained in more detail by citing examples, which should not be construed as limiting. Appropriate modifications may be made within the scope consistent with the gist of the present invention, all of which fall within the technical scope of the present invention.

[0048] Example 1

[0049] Preparation of lithium metal negative electrode: In an argon atmosphere glove box, 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate were mixed in a mass ratio of 84:15:1, DME solvent was added, the content of DME solvent was 30wt%, and the mixture was mixed evenly to obtain a mixture. The mixture was then sprayed onto the surface of the lithium electrode sheet and allowed to stand at 45°C for 5 hours. The lithium metal negative electrode was obtained with an ion conductor layer having a thickness of 2μm.

[0050] Preparation of solid electrolyte membrane: Li 5.54 P 0.98 In 0.02 S 4.4 O 0.1 Cl 1.5 and PTFE binder at a mass ratio of 99:1 for 5 minutes, then roll-pressed at 80°C, gradually narrowing the roll gap to 40 μm, and repeatedly rolling at this roll gap for 60 minutes to obtain a solid electrolyte membrane with a thickness of 40 μm.

[0051] Preparation of positive electrode sheet: LiNi coated with LiNbO3 positive electrode active material 0.9 Co 0.05 Mn 0.05 O2, the coating thickness is 10nm. The positive electrode electrolyte is, for example, the above-mentioned sulfide solid electrolyte, the conductive agent includes Super P and VGCF, and the mass ratio of Super P and VGCF is 1:1, and the binder is HNBR. In an environment with a dew point of -30°C, the positive electrode active material, the positive electrode electrolyte, the conductive agent and the binder are dispersed in xylene, for example, according to a mass ratio of 70:25:2:3, and the amount of xylene added is adjusted to control the solid content of the slurry to 55%. The slurry is coated on aluminum foil by a doctor blade method, and the coated aluminum foil is dried at 100°C for 2h, and then rolled and compacted at 60°C at a pressure of 95MPa to obtain a positive electrode sheet, wherein the thickness of the positive electrode active layer is, for example, 100μm.

[0052] All-solid-state lithium-ion battery assembly: stack the prepared positive electrode sheet, solid electrolyte membrane and lithium metal negative electrode in sequence, so that the solid electrolyte membrane is between the positive electrode sheet and the lithium metal negative electrode to play an isolating role, and stack the sheets to the bare battery cell. Put the bare battery cell into an aluminum-plastic bag, and then stand it, form it and divide it into different volumes to obtain a finished soft-pack solid-state lithium-ion battery.

[0053] Example 2

[0054] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Bi 0.02 S 4.47 O 0.03 Cl 1.5 , other operations remain the same as those in Example 1.

[0055] Example 3

[0056] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 P 0.96 Sb 0.04 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0057] Example 4

[0058] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Al 0.02 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0059] Example 5

[0060] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.54 P 0.98 Ti 0.02 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0061] Example 6

[0062] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 P 0.99 Sb 0.01 S4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0063] Example 7

[0064] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 P 0.8 Sb 0.2 S 4.4 O 0.1 Cl 1.5 , other operations remain the same as those in Example 1.

[0065] Example 8

[0066] The thickness of the ion conductor layer is 0.2 μm, and other operations are the same as those in Example 1.

[0067] Example 9

[0068] The thickness of the ion conductor layer is 5 μm, and other operations are the same as those in Example 1.

[0069] Example 10

[0070] The thickness of the ion conductor layer is 10 μm, and other operations are the same as those in Example 1.

[0071] Embodiment 11

[0072] When preparing the lithium metal negative electrode, 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate were used in a mass ratio of 94:5:1, and other operations were consistent with Example 1.

[0073] Example 12

[0074] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 79:20:1, and the other operations are consistent with Example 1.

[0075] Example 13

[0076] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 69:30:1, and the other operations are consistent with Example 1.

[0077] Embodiment 14

[0078] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 84.5:15:0.5, and the other operations are consistent with Example 1.

[0079] Embodiment 15

[0080] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 80:15:5, and the other operations are consistent with Example 1.

[0081] Example 16

[0082] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 75:15:10, and the other operations are consistent with Example 1.

[0083] Embodiment 17

[0084] When preparing the lithium metal negative electrode, 1,3-dioxolane was replaced by propylene oxide, and other operations were consistent with Example 1.

[0085] Embodiment 18

[0086] When preparing the lithium metal negative electrode, 1,3-dioxolane was replaced by chloromethyl oxirane, and other operations were consistent with Example 1.

[0087] Embodiment 19

[0088] When preparing the lithium metal negative electrode, 1,3-dioxolane was replaced by tetrahydrofuran, and other operations were consistent with Example 1.

[0089] Embodiment 20

[0090] When preparing the lithium metal negative electrode, 1,3-dioxolane was replaced by 1,4-butanediol diglycidyl ether, and other operations were consistent with Example 1.

[0091] Embodiment 21

[0092] When preparing the lithium metal negative electrode, lithium hexafluorophosphate was replaced by lithium bis(fluorosulfonyl)imide, and other operations were consistent with Example 1.

[0093] Embodiment 22

[0094] When preparing the lithium metal negative electrode, lithium hexafluorophosphate was replaced by lithium tetrafluoroborate, and other operations were consistent with Example 1.

[0095] Embodiment 23

[0096] When preparing the lithium metal negative electrode, lithium hexafluorophosphate was replaced by lithium dioxalatoborate, and other operations were consistent with Example 1.

[0097] Embodiment 24

[0098] When preparing the lithium metal negative electrode, silver hexafluorophosphate was replaced by tin difluoride, and other operations were consistent with Example 1.

[0099] Embodiment 25

[0100] When preparing the lithium metal negative electrode, silver hexafluorophosphate was replaced by magnesium difluoride, and other operations were consistent with Example 1.

[0101] Embodiment 26

[0102] When preparing the lithium metal negative electrode, silver hexafluorophosphate was replaced by aluminum tetrafluoroborate, and other operations were consistent with Example 1.

[0103] Embodiment 27

[0104] When preparing the lithium metal negative electrode, the ether monomer is a combination of 1,3-dioxolane and pentaerythritol glycidyl ether, and the molar ratio of the two is 4:1. Other operations are consistent with Example 1.

[0105] Comparative Example 1

[0106] The sulfide solid electrolyte in the solid electrolyte membrane and the positive electrode is changed to Li 5.5 PS 4.5 Cl 1.5 , other operations remain the same as those in Example 1.

[0107] Comparative Example 2

[0108] When preparing the lithium metal negative electrode, the thickness of the ion conductor layer is 0 μm, that is, the lithium matrix is ​​directly stacked with the solid electrolyte membrane, and other operations are consistent with Example 8.

[0109] Comparative Example 3

[0110] When preparing the lithium metal negative electrode, the thickness of the ion conductor layer is 0.05 μm, and other operations are consistent with Example 1.

[0111] Comparative Example 4

[0112] When preparing the lithium metal negative electrode, the thickness of the ion conductor layer is 50 μm, and other operations are consistent with Example 1.

[0113] Comparative Example 5

[0114] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 45:40:15, and the other operations are consistent with Example 1.

[0115] Comparative Example 6

[0116] When preparing the lithium metal negative electrode, the mass ratio of 1,3-dioxolane, lithium hexafluorophosphate and silver hexafluorophosphate is 94.9:5:0.1, and the other operations are consistent with Example 1.

[0117] In Examples 1-27 and Comparative Examples 1-6 of the present invention, all-solid-state lithium-ion batteries are prepared using different sulfide solid electrolytes and lithium metal negative electrodes, and the all-solid-state lithium-ion batteries obtained in Examples 1-27 and Comparative Examples 1-6 are tested. The test results are shown in Table 1.

[0118] In one embodiment of the present invention, the lithium metal negative electrodes obtained in Examples 1-27 and Comparative Examples 1-6 are assembled into a symmetrical battery in the order of lithium metal negative electrode, solid electrolyte membrane, and lithium metal negative electrode. The solid electrolyte membrane is located between the two lithium metal negative electrodes to play an isolating role. The symmetrical battery limiting current density (CCD) is measured. Specifically, 0.1 mA / cm 2 The lithium deposition and stripping tests were carried out for 1 h at a current density of 0.1 mA / cm 2 The increase gradually increases. When the symmetrical battery short-circuits, the test is stopped and the current density at this time is recorded.

[0119] In one embodiment of the present invention, the 0.5C / 0.5C room temperature cycle capacity retention rate test of the all-solid-state ion battery is to charge and discharge the prepared all-solid-state lithium ion battery at a low rate of 0.1C / 0.1C for 2 weeks at 25°C, and the test voltage range is 2.5V~4.2V, and then charge and discharge at a rate of 0.5C / 0.5C, and record the first cycle discharge capacity at 0.5C rate. When the discharge capacity reaches 80% (80% SOH) of the first cycle discharge capacity at 0.5C rate, the test stops and the number of cycles at room temperature is recorded. The calculation formula of the capacity retention rate is as follows: Capacity retention rate (%) = (discharge capacity / discharge capacity of the first cycle) × 100%.

[0120] Table 1. Battery performance test results in Examples 1-27 and Comparative Examples 1-6

[0121]

[0122] Please refer to Table 1. By comparing Examples 1-27 and Comparative Examples 1-2, it can be seen that the combination of the doped modified sulfide solid electrolyte and the lithium metal negative electrode can effectively alleviate the interfacial side reactions between the sulfide solid electrolyte and the lithium metal, regulate the migration and deposition / stripping behavior of lithium ions at the negative electrode, and inhibit the formation of lithium dendrites at high current rates, thereby improving the first efficiency and cycle performance of the all-solid-state lithium-ion battery.

[0123] Please refer to Table 1. By comparing Example 1 and Comparative Examples 1-2, it can be seen that compared with modifying the sulfide solid electrolyte alone or modifying the lithium metal negative electrode alone, the present invention can greatly improve the cycle performance of the all-solid-state lithium-ion battery. The constructed ion conductor layer has good compatibility with the lithium matrix and the doped and modified sulfide solid electrolyte, which effectively reduces the interface impedance and side reactions. The ion conductor layer and the doped and modified solid electrolyte membrane form a stable negative electrode-solid electrolyte interface layer including LiF, Li2O, Li3N, LiCl and an ether polymer formed by ring-opening polymerization at the interface. The interface layer has good ion conductivity and electronic insulation. This stable interface layer can block the direct contact between the sulfide solid electrolyte and the lithium metal negative electrode, and can also make the current and Li on the interface + The flux is homogenized to reduce the risk of lithium dendrite formation.

[0124] Please refer to Table 1. By comparing Examples 1-7 and Comparative Example 1, it can be seen that doping different types of metal elements at the P position has a greater impact on the limiting current density. Among them, the ionic conductivity of indium, bismuth, and antimony elements is better than that of aluminum and titanium elements, and the corresponding all-solid-state lithium-ion battery has better cycle performance. According to Examples 1 and 6-7, it can be seen that regulating the content of the doping element Sb at the P position has a greater impact on the all-solid-state electrochemical performance. When the Sb content is low, for example, 0.01, there is only a small amount of lithium-antimony alloy at the interface of the sulfide solid electrolyte and the lithium metal negative electrode, and the performance improvement of the sulfide all-solid-state lithium-ion battery is not obvious. When the Sb content is high, for example, 0.2, a large amount of Sb2O5 cannot be incorporated into the lattice of the sulfide solid electrolyte, resulting in a rapid decrease in the ionic conductivity of the sulfide solid electrolyte, thereby reducing the limiting current density and deteriorating the performance of the all-solid-state lithium-ion battery.

[0125] Please refer to Table 1. By comparing Example 1, Examples 8-10 and Comparative Examples 2-4, it can be seen that as the thickness of the ion conductor layer increases, the CCD increases first and then decreases, and the cycle performance of the all-solid-state lithium-ion battery increases first and then decreases. When the thickness of the ion conductor layer is less than 2 μm, the inorganic layer formed at the interface is relatively thin, and a huge volume change occurs during long-term lithium deposition / stripping, resulting in the rupture of the inorganic layer and the formation of lithium dendrites; when the ion conductor layer is relatively thick, for example, 50 μm, since the ionic conductivity of the ion conductor layer is lower than that of the sulfide solid electrolyte, Li + It takes more time to pass through this layer of membrane, which will deteriorate the rate performance and energy density of the all-solid-state lithium-ion battery. Therefore, regulating the thickness of the constructed ion conductor layer can further optimize the performance of the all-solid-state lithium-ion battery.

[0126] Please refer to Table 1. By comparing Example 1, Examples 11-27 and Comparative Examples 5-6, it can be seen that the type and content of ether monomers, lithium salts and metal fluorides directly affect the performance of the constructed ion conductor layer. When different types or combinations of ether monomers, lithium salts and metal fluorides are selected, the performance of the all-solid-state lithium-ion battery is different. When the ether monomer is a monocyclic ether, the ring-opening polymerization forms a linear ether polymer; when the ether monomer is a polycyclic ether, the ring-opening polymerization forms a cross-linked ether polymer; when the monocyclic ether and the polycyclic ether exist at the same time, the generated cross-linked ether polymer has better flexibility and can better accommodate the volume change during lithium deposition / stripping. When the content of lithium salt and metal fluoride is low, the carrier concentration of the ion conductor layer is low, ion conduction is hindered, and the lithium alloy and inorganic layer generated on the surface of the lithium matrix are thin, and lithium dendrites still appear during long-term cycling. When the content of lithium salt and metal fluoride is high, the relative content of ether monomers is low, and the strength of the ether polymer formed after ring-opening polymerization decreases. A large amount of lithium salt and metal fluoride are deposited on the surface of the lithium matrix, which is not conducive to ion transport and thus affects the performance of the battery.

[0127] The present invention also provides an electronic device, the electronic device includes at least one of the above-mentioned all-solid-state lithium-ion batteries, and the all-solid-state lithium-ion battery is used to provide electrical energy. Among them, the electronic device can be a vehicle, a mobile phone, a portable device, a laptop computer, a ship, a spacecraft, an electric toy and an electric tool, etc. In one embodiment of the present invention, the vehicle is, for example, a new energy vehicle, and the new energy vehicle can be a pure electric vehicle, a hybrid vehicle or an extended-range vehicle, etc. Spacecraft include airplanes, rockets, space shuttles and spacecrafts, etc. Electric toys include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys and electric airplane toys, etc. Electric tools include metal cutting electric tools, grinding electric tools, assembly electric tools and railway electric tools, such as electric drills, electric grinders, electric wrenches, electric screwdrivers, electric hammers, impact drills, concrete vibrators and electric planers, etc. The electronic device includes the above-mentioned all-solid-state lithium-ion battery, and therefore includes the advantages of the above-mentioned all-solid-state lithium-ion battery, which will not be elaborated here.

[0128] In summary, the present invention proposes an all-solid-state lithium-ion battery and its application, which can improve the stability of the conductivity of the sulfide solid electrolyte, enhance the air stability and improve the electrolyte / active material interface properties, thereby improving the compatibility with the active material. The ion conductor layer has good compatibility with the lithium matrix, can effectively block the direct contact between the sulfide solid electrolyte and the lithium matrix, and inhibit the continuous reaction of the sulfide solid electrolyte. The ion conductor layer has better flexibility, can better accommodate the volume change during lithium deposition / stripping, and can alleviate the volume expansion of the lithium metal negative electrode. By forming a layer of organic-inorganic composite ion conductor layer, the interface impedance can be effectively reduced, the reduction and decomposition of the sulfide solid electrolyte can be blocked, and the electrochemical performance of the sulfide all-solid-state lithium-ion battery can be improved. The sulfide solid electrolyte reacts with the ion conductor layer to form a stable negative electrode-solid electrolyte interface layer. The interface layer has good ionic conductivity and electronic insulation. This stable interface layer can block the direct contact between the sulfide solid electrolyte and the lithium metal negative electrode, and can also make the current and Li on the interface + The flux is homogenized to reduce the risk of lithium dendrite formation.

[0129] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of the invention involved in the present application is not limited to the technical solution formed by a specific combination of the above-mentioned technical features, but should also cover other technical solutions formed by any combination of the above-mentioned technical features or their equivalent features without departing from the inventive concept, such as a technical solution formed by replacing the above-mentioned features with (but not limited to) technical features with similar functions disclosed in this application.

[0130] Except for the technical features described in the specification, the remaining technical features are known technologies to those skilled in the art. In order to highlight the innovative features of the present invention, the remaining technical features will not be described here in detail.

Claims

1. An all-solid-state lithium-ion battery, characterized in that: include: Positive electrode; A lithium metal negative electrode, the lithium metal negative electrode comprising a lithium matrix and an ion conductor layer disposed on one side of the lithium matrix, the ion conductor layer comprising an ether polymer, a lithium salt and a metal fluoride; and A solid electrolyte membrane is disposed between the positive electrode plate and the lithium metal negative electrode. The ion conductor layer is disposed close to the solid electrolyte membrane. The solid electrolyte membrane includes a sulfide solid electrolyte, and the chemical formula of the sulfide solid electrolyte is Li a P 1-b M b S c O d X e , where 5 < a < 6, 0 < b < 1, 1.5 < c < 5, 0 < d < 2.5, 4 < c + d < 5, 1 < e < 2; M is selected from one or more of Al, Ga, In, Ti, Sc, As, Sb, Bi, V, or Nb, and X is selected from one or more of Cl, Br, or I.

2. The all-solid-state lithium-ion battery according to claim 1, characterized in that: M is selected from at least one of Sb, In and Bi, and X is selected from Cl.

3. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The ether polymer is formed by ring-opening polymerization of ether monomers, and the ether monomers include one or more combinations of 1,3-dioxolane, tetrahydrofuran, propylene oxide, chloromethyl ethylene oxide, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, bisphenol A diglycidyl ether or pentaerythritol glycidyl ether.

4. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The lithium salt includes one or more combinations of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorooxalatophosphate, lithium dioxalatoborate or lithium difluorophosphate.

5. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The cations in the metal fluoride include Ag + 、Al 3+ 、Zn 2+ Mg 2+ or Sn 2+ One or more of the following, wherein the anions in the metal fluoride include F - PF6 - 、FSI - TFSI - 、BF4 - PF2O2 - 、ODFB - or ODFP - One or more of .

6. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The ion conductor layer is deposited on the surface of the lithium substrate by spraying or scraping, and the thickness of the ion conductor layer is 0.2 μm to 10 μm.

7. The all-solid-state lithium-ion battery according to claim 1, characterized in that: In the ion conductor layer, the mass ratio of the ether polymer, the lithium salt and the metal fluoride is 60-89.5:10-30:0.5-10.

8. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The thickness of the solid electrolyte membrane is 30 μm to 100 μm.

9. The all-solid-state lithium-ion battery according to claim 1, characterized in that: The solid electrolyte membrane comprises a sulfide solid electrolyte and a binder, wherein the content of the sulfide solid electrolyte in the solid electrolyte membrane is 80wt% to 99wt%; the binder is selected from one or more of polytetrafluoroethylene, polyvinylidene fluoride binder, silicone rubber, styrene-butadiene rubber, nitrile rubber or hydrogenated nitrile rubber.

10. An electronic device, characterized in that: An all-solid-state lithium-ion battery comprising any one of claims 1 to 9.

Citation Information

Patent Citations

  • A method for protecting the negative electrode of a metal secondary battery by a polymer and an application thereof

    CN109103517A

  • Interface modification method for lithium metal negative pole of solid lithium battery

    CN109786675A

  • Non-aqueous electrolyte and secondary battery

    CN114256508A

  • Lithium metal interface protection method and application thereof

    CN116504927A

  • Preparation method and application of lithium argyrodite type solid electrolyte and sulfide film

    CN117457972A